2010
DOI: 10.1093/toxsci/kfq120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hormone Receptor Activities of Pyrethroid Insecticides and Their Metabolites in Reporter Gene Assays

Abstract: Pyrethroid insecticides, the most commonly used insecticides worldwide, are suspected endocrine-disrupting chemicals. But their interactions with hormone receptors are still unclear. The present study intended to evaluate and compare the hormone receptor (estrogen receptor [ER], androgen receptor [AR], and thyroid hormone receptor [TR]) activities of nine pyrethroids (cycloprothrin, cyfluthrin, cyhalothrin, cypermethrin, deltamethrin, etofenprox, fenvalerate, permethrin, and tetramethrin) and their metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(117 citation statements)
references
References 41 publications
6
108
3
Order By: Relevance
“…In the present study, the concentrations at which E2, DHT, and T3 could induce luciferase activities were the same amounts that we have reported previously [25]. The maximal ER activity induced by E2 was 15.8-fold of vehicle control at a concentration of 10 À7 M. For DHT, luciferase activity was significantly increased at 10 À10 M. The maximal induction by DHT was 9.9-fold of vehicle control, which was achieved at a concentration of 10 À7 M. The maximal induction, of 211.5-fold, was induced by T3 at a concentration of 10 À7 M.…”
Section: Hormone Receptor Activities Of Pfossupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, the concentrations at which E2, DHT, and T3 could induce luciferase activities were the same amounts that we have reported previously [25]. The maximal ER activity induced by E2 was 15.8-fold of vehicle control at a concentration of 10 À7 M. For DHT, luciferase activity was significantly increased at 10 À10 M. The maximal induction by DHT was 9.9-fold of vehicle control, which was achieved at a concentration of 10 À7 M. The maximal induction, of 211.5-fold, was induced by T3 at a concentration of 10 À7 M.…”
Section: Hormone Receptor Activities Of Pfossupporting
confidence: 85%
“…The thyroid hormone receptor b (TRb) expression plasmid pGal4-L-TRb and the Gal4-responsive luciferase reporter plasmid pUAS-tk-Luc were used in the TR reporter gene assay. Details of plasmids were previously described [25]. The plasmid phRL-tk, which was used as an internal control for transfection efficiency and the cytotoxicity of PFOS, was purchased from Promega.…”
Section: Cell Line and Plasmidsmentioning
confidence: 99%
“…On the other hand, the application of some veterinary drugs used on dairy farms can be a source of widespread and persistent environment contami-nation that can remain in the soil or water for a period of over 20 years (Gassner et al 1997, Zuccato et al 2000, Iftikhar et al 2014. Highlighting the data found on pesticide residues in raw milk, pyrethroid compounds are toxic and can accumulate in an organism causing severe neurological (Burns et al 2013) and respiratory symptoms (Hudson et al 2014), as well as, can adversely affect endocrine and immune systems (Du et al 2010, Costa et al 2013). a Set by Brazilian Maximum Residue Levels.…”
Section: Resultsmentioning
confidence: 99%
“…All test compounds were prepared as a stock solution in dimethylsulfoxide (DMSO, as a vehicle) at a concentration of 100 mM and stored in the dark at À4 C. The stock solutions were diluted with 50/50% (v/v) Dulbecco's modified Eagle's medium plus Ham's F-12 nutrient mixture (DMEM/F-12; Gibco, Maryland) immediately before use. The final concentration of DMSO in the culture medium did not exceed 0.1% (v/v) and does not affect cell viability (Du et al, 2010). BL21(DE3) Chemically Competent Cell were purchased from Transgene(Peking, China).…”
Section: Methodsmentioning
confidence: 99%
“…Rat studies have shown that pyrethroid insecticides are related to altered serum TH levels (Giray et al, 2010). In another in vitro study 9 pyrethroids were evaluated for potential endocrine disrupting activities via nuclear hormone receptors including TRs using receptor-mediated reporter gene assays in CV-1 cell line, most of the tested compounds exhibited TR antagonistic effects (Du et al, 2010).…”
mentioning
confidence: 99%